2020
DOI: 10.1088/1361-648x/ab9f51
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of amorphous structure under irradiation: zircon case study

Abstract: The nature of the amorphous state has been notably difficult to ascertain at the microscopic level. In addition to the fundamental importance of understanding the amorphous state, potential changes to amorphous structures as a result of radiation damage have direct implications for the pressing problem of nuclear waste encapsulation. Here, we develop new methods to identify and quantify the damage produced by high-energy collision cascades that are applicable to amorphous structures and perform large-scale mol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 27 publications
3
17
1
Order By: Relevance
“…second and third peaks) where no discernible peaks are seen in the fully amorphous structure. This is in agreement with our previous work [10] in which it was shown that even after 6 collision cascades further structural damage and amorphization was still possible. As well as continual change to the local PDFs a continued increase in the number of coordination defects was also observed in the overlapped damaged region.…”
Section: Diffusion In Zirconsupporting
confidence: 94%
See 4 more Smart Citations
“…second and third peaks) where no discernible peaks are seen in the fully amorphous structure. This is in agreement with our previous work [10] in which it was shown that even after 6 collision cascades further structural damage and amorphization was still possible. As well as continual change to the local PDFs a continued increase in the number of coordination defects was also observed in the overlapped damaged region.…”
Section: Diffusion In Zirconsupporting
confidence: 94%
“…In our previous work [10] we showed that the pair distribution function (PDF) of the most highly overlapped damaged region defined by a regular shape of a box containing 6000 atoms was very close to the PDF of the fully amorphous structure. In order to study He diffusion in the damaged structure, we have used a larger region damaged by overlapping collision cascades.…”
Section: Diffusion In Zirconmentioning
confidence: 87%
See 3 more Smart Citations